The Story Of Joseph In Arabic Literature By Siraj Al-Din Al-Mursi Al-Awsi: An Analytical Study/ قصة يوسف في الأدب العربي لسراج الدين المرسي الآوسي: دراسة تحليلية - Bahjat, Munjid Mustafa; Elsawy Bayraktar, Badawy Mohamed; Alhmadani, Mohammed Burhan (Ijaz Arabi Journal of Arabic Learning, 2025)
The research provides an overview and an analytical study of the story of Joseph. The subject of the study is a book written by an obscure scholar of Andalusia, belonging to the tribe of Aws, nicknamed Sirāj al-Dīn, who hails from Murcia, one of the cities of Andalusia. The author titled his book: Zahr al-Kamām fī Qiṣat Yūsuf ʻAlayhi al-Salām. The book has literary, linguistic and missionary value, so the study selected it for analysis. The printed copy in our hands was based on a single handwritten copy, and the editor made a commendable effort in editing it. It was found that the book had many handwritten copies, which the study reviewed, and the necessity of re-editing the book by referring to and benefiting from it was called for. We also did not find a study highlighting the importance of this book. However, the story of Joseph in the past and present is vast, including books and literary works written in Arabic and other Islamic languages. The story of Joseph was reflected in the instinctive talent of Arab poets, who referred to it in their poems. The study focuses on three critical issues in the story: Educational lessons and strengthening our connection with Allah, lessons in management and economics, and social lessons. The study also focuses on the book itself and the author’s methodology in drafting it, whereby the book was divided into seventeen chapters, each of which began with verses from the Qurʼan according to a specific style to emphasize four basic themes to strengthen the meanings of Islam and faith among Muslims. He presented the story of Joseph and the lessons learned from it through these themes. The study adopts the analytical methodology in studying the book by focusing on two fundamental dimensions: the missionary dimension represented by the author through numerical divisions and the linguistic dimension through numerical divisions. The study presents its viewpoint on two prominent areas of the book: The poems mentioned in it, as well as the narrations stated in it, and the opinions of scholars regarding the permissibility of narrating traditions from the Israelites. The study concludes by presenting an appendix related to the effort achieved by the author concerning the poetic quotations included in the book, which numbers 1578 verses of poetry aimed at reinforcing the concepts that the author focused on in his book. The essential results of the study are mentioned in the appropriate sections.